The fifteenth century XV : writing, records and rhetoric - Clark, Linda (Boydell and Brewer : Boydell & Brewer, 2017)
This series (pushes) the boundaries of knowledge and (develops) new trends in approach and understanding. ENGLISH HISTORICAL REVIEW.